Contactless conductivity detection for analytical techniques— Developments from 2014 to 2016. Issue 1 (7th September 2016) - Kubáň, Pavel; Hauser, Peter C.
Abstract : The development of capacitively coupled contactless conductivity detection for the two‐year period from mid‐2014 to mid‐2016 is covered in this review. This includes a survey of fundamental studies and further developments of the measuring technique reported as well as a discussion of new applications. These mostly concern capillary electrophoresis carried out in conventional capillaries as well as on microchip electrophoresis devices. The main focus is on the determination of small non‐UV‐absorbing organic ions and inorganic ions in different types of samples of clinical, nutritional or environmental interest. Outside of electrophoresis contactless conductivity detection is finding uses in detection in column chromatography, flow‐injection analysis and industrial applications.